An Asymmetric Moral Conformity Effect: Subjects Conform to Deontological But Not Consequentialist Majorities - Bostyn, Dries H.; Roets, Arne (Social psychological & personality science, 2017)
The present study investigated whether and to what extent people’s judgments on trolley-type moral dilemmas are subject to conformity pressures. Trolley dilemmas contrast deontological (principled) moral concerns with consequentialist (outcome based) moral reasoning. Subjects were asked to respond to trolley dilemmas in a forced choice format and either simultaneously received bogus information about the base rate of consequentialist and deontological responding for each dilemma or received no distribution information. In the information condition, the bogus distributions showed that either the consequentialist or the deontological choice option was favored by a majority of previous participants. In a set of two independent studies, we showed that subjects exhibit little conformity to a consequentialist majority opinion but strongly conform when confronted with a deontological majority opinion. We suggest this asymmetric conformity effect demonstrates that subjects are less willing to appear consequentialist than deontological, and we explain these results through mutualistic partner choice models.